Explaining Policy Convergence and Polity Divergence in Federal Systems: German and Swiss Higher Education Revisited. Issue 4 (30th March 2018) - Dobbins, Michael; Niemann, Dennis; Martens, Kerstin
Abstract: This article explores higher education reforms in the federally organized education systems of Germany and Switzerland. We argue that the increasing internationalization of education—spearheaded by the Bologna Process—has brought about changes not only in higher education policy, but also led to significant reconfigurations of the higher education polity . These processes present an empirical puzzle: while higher education policies in both systems have broadly moved in the same direction, they have significantly diverged regarding the higher education polity. While Germany has decentralized its higher education system, Switzerland has embraced more centralized structures. Drawing on historical institutionalism, we explain why Germany and Switzerland reacted to essentially identical external challenges with diametrically opposite polity reforms. We contend that this "polity divergence"—despite "policy convergence"—was channeled by the preexisting institutional configurations of educational federalism which steered partisan conflicts along specific paths.